Mixture design experiments applied for the formulation of a textile ink with reproduction of the NATO IRR green color used in military camouflage. Issue 3 (February 2021) - Asofiei, Ioana; Cristian Boscornea, Aurelian; Buliga, Diana-Ioana; Diacon, Aurel; Theodor Tomas, Stefan; Viorica Pop, Cristina
This paper presents the development of a mathematical model for pigment formulations used for screen printing textile inks in order to reproduce the NATO IRR green standard using four highly performant pigments: Hostaperm Yellow H4G (CI 13980), Irgazin Red A2BN (CI 65300), Heliogen Blue (CI 74160), and Lamp Black (CI 77266). In order to study the influence of each pigment on the final CIE L * a * b * parameters, a quadratic mathematical model (Scheffé type) was created and experimentally validated. The model was used and verified for generating pigment compositions for textile inks that reproduce the NATO IRR green. A total of 22 possible solutions were developed and experimentally performed. Studies regarding the reflectance in the visible-near-infrared domain were conducted, ensuring compliance with the standard. The optimal composition of the pigment mixture was 66.55% Hostaperm Yellow H4G, 7.66% Heliogen Blue, 12.01% Irgazin Red A2BN, and 13.78% Irgazin Red A2BN. The mixture was added to textile ink in the proportion of 5% and was applied via serigraphy.